THE LIFE OF ALEKSANDR FEINBERG (Journal of Universal Science Research, 2024)
This article provides information about the life and unique creative activity of the poet Alexander Feinberg, who is Russian and Uzbek. The originality and unusualness of his poems were specially recognized.